Perubahan Sosial, Ekonomi dan Tata Media di Era Penyiaran Digital Studi Kasus Analogue Switch-Off di Indonesia - Witharja, Haris H; Fitriyah, Neka; Muldi, Ali (Jurnal Common, 2023)
Analogue switch-off (ASO) is the process of breaking off an analogue television signal so that digital transmission is completely adopted. Indonesia is currently struggling to move to a total ASO across the country to reap the social and economic benefits of digital conversion. This research specifically uses descriptive research to provide a detailed description of a particular phenomenon. This digitization of television broadcasting can drive better innovation, job creation, productivity and competitiveness, allocating the digital dividend to mobile communications will drive internet adoption and have a huge lucrative economic impact.